2009
DOI: 10.1007/s12011-009-8535-2
|View full text |Cite
|
Sign up to set email alerts
|

Seleno l-Methionine Acts on Cyclophosphamide-Induced Kidney Toxicity

Abstract: The anticancer drug cyclophosphamide (CP) has nephrotoxic effects besides its urotoxicity, which both in turn limit its clinical utility. The nephrotoxicity of CP is less common compared to its urotoxicity, and not much importance has been given for the study of mechanism of CP-induced nephrotoxicity so far. Overproduction of reactive oxygen species (ROS) during inflammation is one of the reasons of the kidney injury. Selenoproteins play crucial roles in regulating ROS and redox status in nearly all tissues; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 26 publications
1
29
0
2
Order By: Relevance
“…5). Contribution of protein nitration, poly(ADPribose)polymerase activation, nicotinamide adenine dinucleotide(±) (NAD±) depletion, lipid peroxidation and GSH depletion in the pathogenesis of CP-induced nephrotoxicity have been reported [11][12][13]. It is well known that carnitine acts as a buffering system by removing accumulated acyl-CoA in mitochondria when the normal metabolic pathway of acyl-CoA is blocked or when acyl-CoA is formed and cannot be further metabolized [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Contribution of protein nitration, poly(ADPribose)polymerase activation, nicotinamide adenine dinucleotide(±) (NAD±) depletion, lipid peroxidation and GSH depletion in the pathogenesis of CP-induced nephrotoxicity have been reported [11][12][13]. It is well known that carnitine acts as a buffering system by removing accumulated acyl-CoA in mitochondria when the normal metabolic pathway of acyl-CoA is blocked or when acyl-CoA is formed and cannot be further metabolized [38].…”
Section: Discussionmentioning
confidence: 99%
“…Abraham et al [10] reported that CP may induce nephrotoxicity secondary to decrease in the activities of lysosomal protein digestive enzymes with consequent accumulation of abnormal amounts of protein in the kidney. Earlier and recent studies have demonstrated that increased generation of both reactive oxygen and nitrogen species by CP in kidney tissues plays a critical role in the pathogenesis of CP-induced kidney damage [9,12,13]. Therefore, compounds such as amifostine and seleno L-methionine prevent CP-induced renal injury by preserving kidney antioxidant parameters from changes caused by CP treatment and, in consequence, prevent oxidative stress and phospholipid peroxidative damage [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the cardiocoxic effects of CP were found to be dose-related cardiac damage, morphologically defined necrosis, bleeding (Ludeman 1999). It has been suggested that in order to benefit from the CP at higher doses, a protective agent was needed that would eliminate the toxic side effects of CP (Ayhanci et al 2010). Plasma antioxidant concentration has shown a decreaseof patients who had a high dose chemotheraphy (Sabuncuoglu and Ozgunes 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In similar study Ayhanci et al investigated protective effects of seleno L-methionine (SLM) in nephrotoxicity induced by CP. they reported that intrapritoneal injection of SLM for 6 days restore GSH values close to the control group, furthermore microscopically observations confirm their work (35). In another study Koss and Lavin investigated adverse effects of CP on various organs in the rat.…”
Section: Discussionmentioning
confidence: 57%
“…CP is a pharmaceutical with an extensive range of medical applications, and it has been proven to be useful in the treatment of cancer (lymphoma, acute and chronic leukemia, and multiple myeloma) as well as non-malignant disorder states such as rheumatoid arthritis (35). It is a well-known bi-function alkylating agent that transfer alkyl residues into a covalent bond with DNA widely used in cancer chemotherapy and expresses its genotoxicity when metabolically activated (36).…”
Section: Discussionmentioning
confidence: 99%